Applied theatre : international case studies and challenges for practice - Prendergast, Monica; Saxton, Juliana, 1933- (Intellect, 2009)
Applied Theatre is the first collection to assist practitioners and students in developing critical frameworks for their own community-based theatrical projects. The editors draw on thirty case studies in applied theatre from fifteen countries—covering a wide range of disciplines, from theatre studies to education, medicine, and law—and collect essential readings to provide a comprehensive survey of the field. Infused with a historical and theoretical overview of practical theatre, Applied Theatre offers clear developmental approaches and models for practical application.